2008
DOI: 10.1159/000161556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volume Used in Sub-Tenon’s Anesthesia on Efficacy and Intraocular Pressure in Vitreoretinal Surgery

Abstract: Purpose: To compare the effect of volumes used in sub- Tenon’s anesthesia on efficacy and intraocular pressure (IOP) in vitreoretinal surgery. Methods: A prospective clinical trial was conducted on patients undergoing sub-Tenon’s anesthesia for vitreoretinal surgery. Patients were randomized to receive either 3-, 5- or 7-ml volumes of anesthetic solution. IOP were measured immediately prior to injection, immediately after injection and at 2, 5 and 10 min after injection. Pain scores were assigned using a numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 58 publications
1
19
1
Order By: Relevance
“…These differing responses in IOP might be due to the differing ethnic patient populations being investigated. Sohn et al suggested that their findings might in part be due to the smaller orbital volume and tighter orbital septum found more commonly among the Asian population 26. The reduction in IOP observed in our study and that of Alwitry et al may be a direct pharmacological effect of the local anaesthetic agent on ocular blood flow, or secondary to a reduction in aqueous production due to an effect on the ciliary ganglion, or possibly because of a reduction in extraocular muscle tone 17…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…These differing responses in IOP might be due to the differing ethnic patient populations being investigated. Sohn et al suggested that their findings might in part be due to the smaller orbital volume and tighter orbital septum found more commonly among the Asian population 26. The reduction in IOP observed in our study and that of Alwitry et al may be a direct pharmacological effect of the local anaesthetic agent on ocular blood flow, or secondary to a reduction in aqueous production due to an effect on the ciliary ganglion, or possibly because of a reduction in extraocular muscle tone 17…”
Section: Discussionsupporting
confidence: 48%
“…IOP is known to rise with increasing volume of local anaesthetic agent used for peribulbar and retrobulbar anaesthesia techniques 24. There are few studies investigating the relationship between volume and IOP after sub-Tenon's anaesthesia 17 25 26. There are no comparative data observing the effect of injecting 10 ml of local anaesthetic into the sub-Tenon space on IOP in the current literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Sohn et al found that injectate volumes above 5 mL produced significant rises in IOP 14. Other work by Gil et al using a 2-quadrant technique with two 5 mL injections showed a prolonged duration of analgesia with no significant rise in IOP in comparison to a single 5 mL injection, although there was a higher incidence (52%) of chemosis 15…”
Section: Methodsmentioning
confidence: 98%
“…However, there are inherent increased risk of morbidities related to higher volume of local anaesthetic agent and multiple injections such as changes in shape and gaze of the globe, myotoxicity, proptosed orbit, conjunctival scarring and increased intraocular pressure. 11 Rise in intraocular pressure can occur in patients with smaller orbital volume and tighter orbital septum -this commonly seen amongst the Asian population [21].…”
Section: Resultsmentioning
confidence: 99%